2002
DOI: 10.1016/s0378-7753(02)00202-1
|View full text |Cite
|
Sign up to set email alerts
|

From molecular models to system analysis for lithium battery electrolytes

Abstract: The behavior of polymer electrolytes in lithium batteries is reviewed in the context of molecular scale models as well as on the system scale. It is shown how the molecular structure of the electrolyte strongly influences ion transport through the polymer as well as across the interfaces and determines the values of a number of parameters needed for system models that can predict the performance of the battery (e.g. κ, D, t+ o and i o ). The interaction of the electrolyte with the electrodes not only leads to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 54 publications
1
46
0
Order By: Relevance
“…And the motion of the ions themselves from one electrolyte site to another is of minor importance. 37 Although perhaps expected for systems such as ours, where the chain length of the tethered ionic liquid is small compared with the diameter of particle core, the VFT dependence implies that the ionic conductivity of the SiO 2 -IL-TFSI/LiTFSI mixtures can be understood in terms of local segmental and breathing motions of molecules in the materials. Fig.…”
Section: Resultsmentioning
confidence: 92%
“…And the motion of the ions themselves from one electrolyte site to another is of minor importance. 37 Although perhaps expected for systems such as ours, where the chain length of the tethered ionic liquid is small compared with the diameter of particle core, the VFT dependence implies that the ionic conductivity of the SiO 2 -IL-TFSI/LiTFSI mixtures can be understood in terms of local segmental and breathing motions of molecules in the materials. Fig.…”
Section: Resultsmentioning
confidence: 92%
“…6 Polyoxetanes are polyethers that contain trimethylene oxide units and can also be used as a polymer matrix for PEs. [10][11][12] PEs based on polyoxetanes with polar side chains, such as nitrile groups and phosphate ester groups, were reported. [13][14][15] The increase in glass transition temperature (T g ) associated with complexation with Li + ions, which is a typical behavior for PEs, does not occur in poly(3-(2cyanoethoxymethyl)-3-ethyloxetane) (PCEO); rather, T g decreases with increasing salt concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Although recent work by Zhang et al and Gadjourova at el. demonstrated that ion conduction is possible in crystalline polymers [33,34], the majority of the previous studies focused on the amorphous phase, where ion transport is dependent on the segmental motion of the polymer chains [35][36][37][38][39][40]. When lithium salts are introduced to the polymer matrix forming PEO/LiX complexes, the oxygen atoms from both the PEO chains and the anions coordinate the lithium ions [41].…”
Section: Introductionmentioning
confidence: 99%